PROFIT AND LOSSES OF THE NICKEL DOWNSTREAM PROGRAM FOR THE INDONESIAN ECONOMY - Hudjolly; Ahmad Rizani; Andri Triyantoro; Muhammad Lucky; Wahyudi Umar (Adisam Publisher, 2024)
One of the hot and endless discussions is regarding Nickel Downstreaming in Indonesia. one of the parts assesses that the policy of stopping nickel ore exports has an effect on improving the Indonesian economy. Indonesia is one of the ten countries with the largest nickel reserves in the world. Nearly 4 million metric tons of the world's 80 million metric tons of nickel reserves are stored in Indonesia. With 5.74% of the world's total nickel reserves, Indonesia is ranked 6th in the world's largest nickel producer and Indonesia's nickel production increases every year. Indonesia to issue policy Regulation of the Minister of Energy and Mineral Resources Number 11 of 2019 concerning nickel downstreaming. Nickel downstreaming is an act of protectionism or limiting nickel exports in world trade. The purpose of this study is to analyze the reasons why Indonesia has taken protectionist measures against its nickel. This research is qualitative research with a descriptive approach. The Research use research data in the form of secondary data obtained from a number of credible sources such as scientific articles, books, and a number of other sources that are credible and commonly used in research. These data were analyzed using analytical tools with stages of data collection, data selection, data reduction and drawing conclusions.